Influence of crystal orientation and Berkovich tip rotation on the mechanical characterization of grain boundaries in molybdenum. (15th November 2019) - Jakob, S.; Leitner, A.; Lorich, A.; Eidenberger-Schober, M.; Knabl, W.; Pippan, R.; Clemens, H.; Maier-Kiener, V.
Abstract: In this study, nanoindentation experiments with a continuously measured stiffness are performed in the vicinity of grain boundaries in technically pure molybdenum. A significant change in hardness as a function of indentation depth is put in context with the corresponding deformation patterns in the indented crystals. The difference in hardness increase of 18% compared to 5% of two different grain boundaries with similar misorientation angle could be explained in this way. Five degrees of freedom have to be determined to fully describe a grain boundary. However, the influence of the rotation angle of a pyramidal indenter geometry around the loading axis as yet another loading parameter is assessed by backscattered electron micrographs and orientation deviation maps. Indentation experiments with different rotation angle at the same grain boundary confirm that a hardness increase close to the grain boundary is only apparent if a significant amount of plastic deformation is introduced towards the interface. Graphical abstract: Unlabelled Image Highlights: Increased hardness in the vicinity of grain boundaries is only apparent if deformation is introduced towards the interface. Deformation patterns form along crystallographic directions and are influenced by the rotation of a pyramidal indenter tip. Spherical indentation can reveal the intrinsic deformation paths without the influence of indenter rotation.